IMPLEMENTATION OF PRO BONO IN THE ADVOCATE PROFESSION - Arifin, Syamsul; Shodiq, Ja'far; Albab, Ulil; Septiani, Dina Florensia (Universitas Islam Lamongan, 2023)
Abstract Advocates in undergoing the litigation process get the title of officium nobile. The honourable title that advocates have is to see their role in guarding law enforcement. The expected law enforcement is the concern and role of advocates in helping underprivileged people. Legal aid to the underprivileged is known as pro bono. The study in this research uses a juridical-normative approach by referring to laws and books related to the implementation of pro bono for advocates. The process of applying for pro bono is by following the laws and regulations that have been in force in Indonesia. Adhering to Government Regulation No. 83/2008 and Law No. 16/2011.